2002
DOI: 10.1029/2001jd000524
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical cycling of carbon, water, energy, trace gases, and aerosols in Amazonia: The LBA‐EUSTACH experiments

Abstract: [1] The biogeochemical cycling of carbon, water, energy, aerosols, and trace gases in the Amazon Basin was investigated in the project European Studies on Trace Gases and Atmospheric Chemistry as a Contribution to the Large-Scale Biosphere-Atmosphere Experiment in Amazonia (LBA-EUSTACH). We present an overview of the design of the project, the measurement sites and methods, and the meteorological conditions during the experiment. The main results from LBA-EUSTACH are: Eddy correlation studies in three regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
315
1
29

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 358 publications
(367 citation statements)
references
References 96 publications
22
315
1
29
Order By: Relevance
“…During night, the calculated chemical loss partly exceeds the storage corrected flux, which may be attributed to the considerably large uncertainty of the flux and profile measurements, when O 3 sensors are close to their detection limits. During the dry season experiment the chemical term was generally enhanced due to higher O 3 , but also NO mixing ratios (see Andreae et al, 2002). Particularly during night, the chemical term explains a considerable part (in the second half even the major part) of the ozone deposition (Fig.…”
Section: Ozone Flux and Deposition Budget Termsmentioning
confidence: 99%
“…During night, the calculated chemical loss partly exceeds the storage corrected flux, which may be attributed to the considerably large uncertainty of the flux and profile measurements, when O 3 sensors are close to their detection limits. During the dry season experiment the chemical term was generally enhanced due to higher O 3 , but also NO mixing ratios (see Andreae et al, 2002). Particularly during night, the chemical term explains a considerable part (in the second half even the major part) of the ozone deposition (Fig.…”
Section: Ozone Flux and Deposition Budget Termsmentioning
confidence: 99%
“…These authors stated that bee pollen is an extremely hygroscopic material, which can be affected by environmental conditions. For this reason, it is likely that the samples used in the present study showed a high moisture content, as they were collected in a period (March) when the air relative humidity is usually high and the atmospheric precipitations are intense in the Amazon region (ANDREAE et al, 2002). The high moisture content of meliponine-collected pollen can favor fermentation processes, which are characteristic of stingless bee pollen.…”
Section: Moisturementioning
confidence: 99%
“…The site normally experiences a mean annual rainfall of 1600-2100 mm and has a pronounced dry season between June and August, whereas the wettest periods are between December and April (Gash et al . 1996;Andreae et al . 2002).…”
Section: Sampling Sites and Periodsmentioning
confidence: 99%